Recent advances in higher order rotaxane architectures - Zhou, He-Ye; Zong, Qian-Shou; Han, Ying; Chen, Chuan-Feng (Chemical communications (Cambridge, England), 2020)
Despite dramatic advances in the template-directed synthesis of archetypal [2]rotaxanes, higher order rotaxanes with multiple molecular components (rings or dumbbells) are relatively daunting subjects owing to their synthetic challenges. With unique interlocked architectures, higher order rotaxanes have found applications in artificial molecular machines. In this feature article, we will focus on the recent advances in higher order rotaxanes with well-defined structures. Different types of rotaxane architectures will be described, and their synthetic approaches will be highlighted. Moreover, the stimuli-responsive molecular motion with increasing complexity in these diverse architectures will also be discussed. Recent advances in various types of higher order rotaxanes with precisely controlled architectures are summarized in this feature article.